The influence of storage conditions on flavour changes in human milk. - Spitzer, Johanna; Doucet, Sèbastien; Büttner, Andrea (Food Quality and Preference, 2010)
The effects of freeze-storage on human milk have been investigated with regard to sensory changes and modifications in the molecular composition of constituent odour-active volatiles. Sensory evaluation showed that fishy-metallic odour attributes are generated during storage, as are rancid-sweaty odour notes, which were described by panellists to be highly unpleasant. To monitor the dynamics of off-odour development in human milk, sensory evaluation in both orthonasal and retronasal mode was performed at defined time intervals of storage, with parallel evaluation of human milk samples that had been heated prior to freeze-storage. Heating was found to induce slight flavour changes, with generation of a predominantly egg-white-like note, but with no further generation of off-odour formation upon subsequent storage. This suggests that the formation of the off-odour in non-heated milk resulted from metabolic processes in the milk, although may also be due to the specific composition of human milk. In comparison, similar off-odour development was not observed in bovine milk. Molecular identification of the off-odour substances, most specifically free fatty acids and oxidation derivatives of polyunsaturated fatty acids, indicated both lipolytic and peroxidative processes of components of the native human milk. Finally, these results indicate that human milk is obviously a highly sensitive food material, specifically with regard to its characteristic fatty acid composition.<br